Modeling Accessible Streets and Sidewalks in South Sulawesi, Indonesia - Muhammadiah, M. Jabir; Selao, Ahmad; Ladung, Fajar (The Center for Disability Studies and Services Brawijaya University, 2025)
This study investigates the accessibility of public spaces, particularly roads and sidewalks, for persons with disabilities in the city of South Sulawesi, Indonesia. This research is driven by the critical need to create an inclusive environment that serves all individuals, emphasized by the UN Convention on the Rights of Persons with Disabilities and Indonesian Law No. 8/2016. The purpose of this research is to evaluate infrastructure, identify obstacles faced by individuals with disabilities, and propose a model of disability-friendly public spaces. We used case study methods, focusing on the city of Parepare which involve the collection of in-depth interview data with people with disabilities, public space managers, and government officials, direct observation of roads and sidewalks, and analysis of relevant policy and regulation. We used thematic analysis to analyze the collected data, identifying key themes related to accessibility challenges and potential solutions. These findings reveal that the streets and sidewalks of Parepare often lack adequate accessibility features, such as sufficient width, smooth surfaces, and clear signage. Obstacles such as utility poles and parked vehicles further hinder mobility. The implication is the need for improved infrastructure design, policy implementation, and public awareness to enhance the quality of life for people with disabilities. This study recommends enhancing collaboration with the disability community, conducting regular audits of public spaces, and implementing universal design principles to create an inclusive environment and make Parepare a Disability Smart City (DSC).